Explaining software developer acceptance of methodologies a comparison of five theoretical models. - Riemenschneider, C.K.
Many organizations attempt to deploy methodologies intended to improve software development processes. However, resistance by individual software developers against using such methodologies often obstructs their successful deployment. To better explain why individual developers accept or resist methodologies, five theoretical models of individual intentions to accept information technology tools were examined. In a field study of 128 developers in a large organization that implemented a methodology, each model explained significant variance in developers' intentions to use the methodology. Similar to findings from the tool adoption context, we found that, if a methodology is not regarded as useful by developers, its prospects for successful deployment may be severely undermined. In contrast to the typical pattern of findings in a tool context, however, we found that methodology adoption intentions are driven by: 1) the presence of an organizational mandate to use the methodology, 2) the compatibility of the methodology with how developers perform their work, and 3) the opinions of developers' coworkers and supervisors toward using the methodology. Collectively, these results provide surprising new insights into why software developers accept or resist methodologies and suggest what software engineering managers might do to overcome developer resistance.
Keywords: Information technology tools; Software developer acceptance; Software developers; Software development processes; Software engineering managers; Tool adoption context